Different forms movement therapy used in rehabilitation of Parkinson's disease - Strojek, Katarzyna; Karpińska, Anna; Piekorz, Zuzanna; Zukow, Walery; Radzimińska, Agnieszka (Journal of Education, Health and Sport, 2018)
The causes of Parkinson's disease have not yet been strictly defined, which is why it is a serious social problem nowadays. The problem stems mainly from the fact that pharmacological methods have not been developed to such an extent to completely cure the disease. Due to the application of those methods, it is primarily expected to cause the delay in the development of disease symptoms. An important role in the reduction of progressive disease symptoms is performed by non-pharmacological forms of rehabilitation. In addition to standard kinesitherapy, the following are of great therapeutic importance: choreotherapy, music therapy, massage, physical therapy, and balneotherapy. The use of these methods positively affects the general state of physical fitness of the patient, moreover, it contributes to the delay in the development of characteristic symptoms of Parkinson's disease such as muscle stiffness, tremor, and slowness of movement. The variety of implemented interventions not only improves the patient's functional status but also contributes to the increase of self-esteem and psychological well-being.